Pandemic-Proofing Your Library: Disaster Response and Lessons Learned from COVID-19. Issue 1 (2nd January 2021) - Koos, Jessica A.; Scheinfeld, Laurel; Larson, Christopher
Abstract: The COVID-19 pandemic has affected libraries across the globe, including academic health sciences libraries, in many ways. This manuscript describes the challenges, solutions, and practices employed by the Stony Brook University Health Sciences Library in order to maintain continuity of services to patrons including faculty, hospital staff, students, and clinicians while operating in one of the earliest epicenters of the pandemic. Some of the major changes the library underwent in response to the pandemic included implementing new online anatomy resources, contactless circulation, remote interlibrary loan services and modified operating practices.